Improvement of a new acoustic emission analysis technique to determine the activated carbon saturation level: A comparative study. Issue 2 (April 2020) - Mariño Peacok, Thayset; Crespo Sariol, Harold; Yperman, Jan; Sánchez Roca, Ángel; Carleer, Robert; Puente Torres, Jeamichel; Reggers, Guy; Haeldermans, Tom; Thijssen, Elsy; Samyn, Pieter; Gryglewicz, Grazyna; Salomón García, Liset
Highlights: Acoustic emission analysis (AEA) is a sensitive technique to characterise activated carbons. AEA can quantify the exhaustion level of the different layers in a GAC filte. AEA is also an alternative method for nitrogen adsorption (BET analysis). TGA, XRF and Elemental Analysis are used to validate the acoustic emission results. AEA offers a solution for monitoring a correct management of GAC application. Abstract: A new Acoustic Emission Analysis (AEA) method has been successfully applied to quantify the exhaustion degree in an industrial granular activated carbon (GAC) filter for water treatment in different industrial processes. Five samples of GAC obtained at different depths of the target industrial filter have been evaluated. For the first time the analysis of the acoustic energy and the signal power was applied, besides the processing of signal its frequency, amplitude and integral area under the signal envelope curve. The envelope and energy of the acoustic signal were mathematically processed using Gilbert and Parseval theorems. Additionally, image segmentation techniques are applied to analyze spectrograms in order to determine the exhaustion level of the GAC samples. Acoustic emission results are discussed in terms of CaCO3 adsorption mechanisms in the water filter and correlated with dedicated analytical methods such as TGA, SEM, FTIR, XRF and N2 gas adsorption. The implementation of AEA in engine power plants in Cuba constitutes an interesting approach to implement an improved strategy of GAC management in water treatment industries.